Expansion of breeding habitat brown skua Chatharacta antarctica (Lesson, 1831) near Ukrainian Antarctic station Academic Vernadsky - D. V. Pilipenko (Ukrainian Antarctic Journal, 2012)
The study of the avifauna in the Argentine Islands held a long time, almost since their discovery, but they are mainly related to the colonial species. Over the entire study period there were found 27 species of birds, 10 of which were nesting, but also for a nest is not excluded. In a period of 15 UAE, in season 2010/2011 we conducted the study avifauna of the region and identified 17 species of birds, of which 11 confirmed nesting. Including a new breeding species for which nests only previously anticipated.